Classic Batik Cakes / Nur Munawwarah Mohd Zairul, Muhammad Shafizal Hakimi Mohd Shafee and Amir Razin Ruslan - Mohd Zairul, Nur Munawwarah; Mohd Shafee, Muhammad Shafizal Hakimi; Ruslan, Amir Razin (2022)
Classic Batik Cafes is an online business that got its start primarily through the social networking site Facebook. It was founded in the year 2022 and is mostly focused on the sale of food. Our consumers' sugar appetites can be satisfied by batik cakes. It also can bring benefit to their health. The fundamental concept behind our company is to sell batik cakes that are both sweet and delicious. All of the ingredients used are of high quality and do not include any dangerous elements. Classic Batik Cakes, Indulgence Batik Cakes, and Oreo Batik Cakes were the three products that we provided for our customers' enjoyment. Kementerian Kesihatan Malaysia (KKM) has certified all of this product, and there have been overwhelmingly positive comments on this particular product. For the business, our target segmentation includes both men and women, regardless of their age. As we all know, the majority of individuals have a preference for sweetness, which can appeal to the palate of anyone, whether they are 10-year-old children or 65-year-old grandparents. The information that we are sharing with our customers will assist customers in providing relevant information. We use our Facebook page as a business platform for our Classic Batik Cakes in order to reach a larger audience. Facebook is truly one of the most effective social media platforms for businesses, as it helps them to communicate and interact with customers effectively. It makes it easy for us to launch teasers, do soft sells, and hard sells in our business. Utilizing social media platforms has enabled us to plan our marketing approach. It allows us to provide seven teasers, 16 graphic and postings for soft sell and hard sell. We try any method in order to fulfil the AIDCA and TISCta, such adding a caption to the post and designing a unique and fascinating graphic to draw the attention of our customers. A more in-depth explanation is provided further down the page